Analysis of The Impact of Work Interaction, K3 Culture, and Motivation on Employee Performance - Rudy Surapto; Rumanintya Lisaria Putri; Roosganda Elizabeth (Malikussaleh University, Aceh, Indonesia, 2023)
Interaction between employees with various backgrounds, employee motivation, and safety culture are part of the chain and integrated aspects to achieve good employee performance. This study aims to analyze the effect of work interaction, safety culture, and work motivation on employee performance at the Underground Maintenance Department, PTFI, Papua, Indonesia. This research is explanatory research, which explains the causal relationship between research variables and hypothesis testing. The results showed a significant and simultaneous influence between work interaction, safety culture, and work motivation on employee performance in the Underground Maintenance Department. In addition, the work motivation variable has a dominant force on performance within the department.